Using rich picture as a didactic resource based on visual thinking (Research, Society and Development, 2020)
Information representation techniques can promote knowledge through visual thinking, aiding in the teaching and learning of various subjects in different areas of knowledge. Considering this, this article aims to analyze the use of rich picture as a didactic resource for teaching based on visual thinking. The paper presents an experience report that constitutes a qualitative study, in which the rich picture was used as a didactic resource in an undergraduate course taught for a Software Engineering course. The results of the experiment underscore the potential for using rich picture in disciplines that adopt problem-situation analysis as a teaching strategy, as it enables the analysis of complex relationships. The study also highlights that adopting the rich picture as a didactic resource requires prior planning, identifying its suitability to the learning objectives involved and the content of the subject.